2008
DOI: 10.1291/hypres.31.127
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Insulin Infusion Normalizes Blood Pressure and the Gene Expressions of Angiotensin II Type 1 Receptor in Fructose-Fed Rats

Abstract: It remains open to debate whether hyperinsulinemia leads to the development of hypertension. We addressed this issue by investigating the effect of chronic insulin infusion on blood pressure and related parameters in hypertensive fructose-fed rats. Rats were given either normal chow or a fructose-rich diet, and insulin or saline was infused through mini-pumps in the same animals for 14 days. The chronic insulin infusion exerted no effect on the blood pressure of the chow-fed rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Thus, the RAS is a reasonable target for prevention of fructose-induced cardiovascular pathologies. It was shown previously that FRD induces a cluster of abnormalities, including hypertension, hypertriglyceridemia, and glucose intolerance in addition to hyperinsulinemia [20], which is in agreement with our results. The ACE and AT 1 receptor upregulated by FRD in this study have been involved in the insulin resistance, also an early phenotype of metabolic syndrome.…”
supporting
confidence: 94%
See 1 more Smart Citation
“…Thus, the RAS is a reasonable target for prevention of fructose-induced cardiovascular pathologies. It was shown previously that FRD induces a cluster of abnormalities, including hypertension, hypertriglyceridemia, and glucose intolerance in addition to hyperinsulinemia [20], which is in agreement with our results. The ACE and AT 1 receptor upregulated by FRD in this study have been involved in the insulin resistance, also an early phenotype of metabolic syndrome.…”
supporting
confidence: 94%
“…It was previously demonstrated that FRD affects the expression of ACE in aortas and AT 1 receptor in hearts and aortas of male rats [9]. Other study also showed upregulation of AT 1 receptor mRNA and unchanged AT 2 receptor mRNA in aorta under the 60 % FRD [20]. Prolonged AT 1 receptor activation leads to myocyte hypertrophy, which becomes a major risk factor for congestive heart failure, sudden cardiac death, and overall mortality [21].…”
mentioning
confidence: 93%
“…Experimental evidence suggests that in MetS, the RAS axis composed of ACE/AT1r is activated. A high-fructose diet can be used an experimental model to increase systolic blood pressure by activating the ACE/ AT1r axis [7,8]. Through AT1r, angiotensin-II can exert its pro-inflammatory effects.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have already shown that fructose rich diet increases AngII level in the plasma (Giani et al 2010;Zhou et al 2012;Tran et al 2014;Kobayashi et al 1993;Farah et al 2006;Fukui et al 2008;Tran et al 2009). It was shown in earlier studies that AngII induces nuclear sequestration of AT1 receptor from the plasma membrane, in brain neurons and vascular smooth muscle cells (Lu et al 1998;Bkaily et al 2003).…”
Section: R a F Tmentioning
confidence: 97%